NKTR-214 immunotherapy synergizes with radiotherapy to stimulate systemic CD8+ T cell responses capable of curing multi-focal cancer - William L Redmond; Ute Hoch; Melissa J Kasiewicz; Michael J McNamara; Deborah H Charych; Joshua M Walker; Annah S Rolig; Daniel C Rose; Ian F Hilgart-Martiszus (Journal for ImmunoTherapy of Cancer, 2020)
Background High-dose radiotherapy (RT) is known to be immunogenic, but is rarely capable of driving clinically relevant abscopal antitumor immunity as monotherapy. RT is known to increase antigen presentation, type I/II interferon responses, and immune cell trafficking to irradiated tumors. Bempegaldesleukin (NKTR-214) is a CD122-preferential interleukin 2 (IL-2) pathway agonist that has been shown to increase tumor-infiltrating lymphocytes, T cell clonality, and increase PD-1 expression. NKTR-214 has increased drug half-life, decreased toxicity, and increased CD8+ T cell and natural killer cell stimulation compared with IL-2.Methods Animals bearing bilateral subcutaneous MCA-205 fibrosarcoma or CT26 colorectal tumors were treated with NKTR-214, RT, or combination therapy, and tumor growth of irradiated and abscopal lesions was assessed. Focal RT was delivered using a small animal radiation research platform. Peripheral and tumor-infiltrating immune phenotype and functional analyses were performed by flow cytometry. RNA expression profiling from both irradiated and abscopal lesions was performed using microarray.Results We demonstrate synergy between RT of a single tumor and NKTR-214 systemic therapy resulting in dramatically increased cure rates of mice bearing bilateral tumors compared with RT or NKTR-214 therapy alone. Combination therapy resulted in increased magnitude and effector function of tumor-specific CD8+ T cell responses and increased trafficking of these T cells to both irradiated and distant, unirradiated, tumors.Conclusions Given the increasing role of hypofractionated and stereotactic body RT as standard of care treatments in the management of locally advanced and metastatic cancer, these data have important implications for future clinical trial development. The combination of RT and NKTR-214 therapy potently stimulates systemic antitumor immunity and should be evaluated for the treatment of patients with locally advanced and metastatic solid tumors.